Efficacy and Safety of First-Line Immunotherapy in Combination with Chemotherapy for Patients with Extensive-Stage Small Cell Lung Cancer: A Systematic Review and Network Meta-Analysis. (29th September 2020) - Wang, Bi-Cheng; Xiao, Bo-Ya; Li, Peng-Cheng; Kuang, Bo-Hua; Chen, Wang-Bing; Li, Pin-Dong; Lin, Guo-He; Liu, Quentin
Abstract : Background . The prognosis of patients with extensive-stage small cell lung cancer (SCLC) is poor. Adding an immune checkpoint inhibitor (ICI) to chemotherapy may exert a synergistic effect and improve survival outcomes. However, for treatment-naive extensive-stage SCLC patients, the efficacy of immunotherapy in combination with cytotoxic chemotherapy remains controversial. Objective . To evaluate the benefits and risks of the combination of immunotherapy and chemotherapy and to assess the comparative effectiveness of different first-line treatment strategies for extensive-stage SCLC. Methods . PubMed, Web of Science, EMBASE, and Cochrane Library were searched for randomized clinical trials studying different immunotherapeutics for patients with previously untreated extensive-stage SCLC up to Feb 16, 2020. The primary outcomes were overall survival (OS) and progression-free survival (PFS), and the secondary outcomes were objective response rate (ORR), disease control rate (DCR), and adverse events. Results . We identified 141 published records, and 4 studies (comprising 2202 patients) were included in the analysis. Immunotherapy (including ipilimumab, atezolizumab, and durvalumab) plus chemotherapy was associated with better OS (hazard ratio (HR) 0.84, 95% confidence interval (CI) 0.75–0.93; risk ratio (RR) 0.90, 95% CI 0.81–1.00) and PFS (HR: 0.81, 95% CI 0.74–0.88; RR 0.96, 95% CI 0.93–0.99) than placebo plus chemotherapy. The addition of immunotherapy to chemotherapy showed similar improvement in ORR, DCR, and adverse events versus placebo plus chemotherapy. On the surface under the cumulative ranking (SUCRA) analysis, the anti-PD-L1 agent, atezolizumab, had the highest likelihood of achieving improved OS (93.4%) and PFS (95.0%). Conclusion . In the first-line setting, combining immunotherapy with chemotherapy is better than standard chemotherapy in terms of OS and PFS. Across the eligible studies, PD-L1 inhibitors might be preferred. Further explorations of more ICIs in the first-line treatment for extensive-stage SCLC patients should be needed.